2022
DOI: 10.1186/s12866-022-02568-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR using atpE, conventional PCR targeting different regions of difference, and flow cytometry for confirmation of Mycobacterium bovis in buffaloes and cattle from the Delta area of Egypt

Abstract: Background Mycobacterium bovis notoriously causes detrimental infections in bovines and humans. In this study, 1500 buffaloes and 2200 cattle were tested by single intradermal comparative cervical tuberculin test and compared with the detection rates of M. bovis isolation, real-time and simplex PCR, and flow Cytometry. Results The tuberculin test is the reference test in Egypt, the positive rate was 54/3700 (1.5%) composed of 18/1500 (1.2%) buffalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…With the increase in the number of bacteria, further humoral immunity is produced, and the animals Studies have shown that BTB can also be diagnosed by direct immunofluorescence staining of surface antigen epitopes on peripheral blood monocytes (Figure 2). Elsayed et al [26] used real-time PCR, traditional PCR, and flow cytometry to compare the detection rate of bovine tuberculosis. The results showed that the sensitivity and specificity of real-time PCR and flow cytometry were 100% and 100%, respectively, while the sensitivity and specificity of conventional PCR for different RDs were 81.48% and 100%, respectively.…”
Section: Application In the Diagnosis Of Bovine Tuberculosismentioning
confidence: 99%
“…With the increase in the number of bacteria, further humoral immunity is produced, and the animals Studies have shown that BTB can also be diagnosed by direct immunofluorescence staining of surface antigen epitopes on peripheral blood monocytes (Figure 2). Elsayed et al [26] used real-time PCR, traditional PCR, and flow cytometry to compare the detection rate of bovine tuberculosis. The results showed that the sensitivity and specificity of real-time PCR and flow cytometry were 100% and 100%, respectively, while the sensitivity and specificity of conventional PCR for different RDs were 81.48% and 100%, respectively.…”
Section: Application In the Diagnosis Of Bovine Tuberculosismentioning
confidence: 99%